Awesome Dog 5000 vs. the Kitty-Cat Cyber Squad - Dean, Justin (New York : Random House, 2021)
"Marty, Ralph, and Skyler create their own superhero personas, while Awesome Dog's biggest fan becomes Townville's newest supervillain and creates a team of robot kittens that challenge the robot dog in his most dangerous battle yet"--
Keywords: Robots -- Juvenile fiction; Dogs -- Juvenile fiction; Cats -- Juvenile fiction; Adventure stories; Superheroes -- Juvenile fiction; Supervillains -- Juvenile fiction; Science fiction